Gaya Kepemimpinan dalam Lembaga Pendidikan - Dimas Zuhri Ahmad; Abdullah Muqopie; Anis Zohriah; Anis Fauzi (Departement of Mathematics Education, 2023)
Leadership type and style are closely related to the norms of behavior in a person while influencing affects the behavior of others. Leadership types and styles have various variants, so there is a need for a theoretical study that discusses leadership types and styles This research is a literature review of several main references. This type and style of leadership is not necessarily like that, but always develops from time to time. As a suggestion made by the next researcher is to examine the type and style of leadership with various examples of cases found in various places and conditions by comparing the theory and practice carried out.